2017
DOI: 10.1007/s10803-017-3315-x
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Self-Reported Academic, Social, and Mental Health Experiences of Post-Secondary Students with Autism Spectrum Disorder

Abstract: Increasing numbers of individuals with autism spectrum disorder (ASD) are enrolling in post-secondary academic institutions. However, research indicates that post-secondary students with ASD are struggling more than their typically developing peers, with high rates of loneliness, anxiety, depression, and an increased incidence of dropping-out before completion of their degrees. The current study utilized an online survey to gain insight into the self-reported academic, social, and mental health experiences of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
100
1
10

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(133 citation statements)
references
References 25 publications
(35 reference statements)
10
100
1
10
Order By: Relevance
“…Supporting findings from prior work, individuals with ASD self‐reported feelings of academic competence, and did not differ from typically developing peers in intellectual engagement [Jackson, Hart, Brown, & Volkmar, ]. However, more targeted academic support services may be required for individuals with ASD and comorbid LD and/or ADHD.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Supporting findings from prior work, individuals with ASD self‐reported feelings of academic competence, and did not differ from typically developing peers in intellectual engagement [Jackson, Hart, Brown, & Volkmar, ]. However, more targeted academic support services may be required for individuals with ASD and comorbid LD and/or ADHD.…”
Section: Discussionsupporting
confidence: 61%
“…Many postsecondary students with ASD report feeling incredibly lonely and isolated while enrolled in postsecondary education [Anderson, Carter, & Stephenson, ; Anderson et al, ; Gelbar et al, ; Jackson, Hart, Brown, & Volkmar, ]. Interpersonal self‐confidence is one important component of social communication, and is associated with better communication skills and interpersonal problem solving skills [Erozkan, ], and when impaired, can result in greater interpersonal stress [Matsushima & Shiomi, ] and depression [Marton, Connolly, Kutcher, & Korenblum, ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Newman et al [], however, reported that students with ASD had a lower likelihood of completing their degree (38.8%) compared to students from the general population (52.4%) and to those with disabilities in general (40.7%). Additionally, among studies describing the feelings of students with ASD, anxiety was most common, followed by loneliness, depression, and feelings of isolation from peers [Gelbar et al, ; Jackson, Hart, Brown, & Volkmar, ; White, Ollendick, & Bray, ]. In a survey study conducted in Australia, students reported an ability to cope with their academic workload but frequent struggling with mental health issues: anxiety (90.2%), depression (70.7%), and loneliness (61%) were reported as “moderate” to “big” concerns [Anderson, Carter, & Stephenson, ]; similar findings were reported among American students in another survey study [Jackson et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports suggest that although around half (46%) of autistic students have the intellectual potential (Centers for Disease Control and Prevention 2012) to attend higher education (Sanford et al 2011), the number of enrolment, retention, academic achievements, and employment rate following graduation is still relatively lower compared to students with other disabilities, as well as their typically developing peers (AGCAS Disability Task Group 2014; Gobbo and Shmulsky 2014;Lucas and James 2018). A recent report (Jackson et al 2018) also found in a sample of 56 autistic adults currently enrolled in post-secondary institutions in the US, UK, and Canada, around three quarters reported feelings of isolation, high levels of stress, anxiety, depression, and suicidal ideation, further highlighting the poor state of mental health for many autistic students when transitioning to university. Furthermore, completing post-secondary education often did not serve as a direct stepping stone for many autistic students, as participation in competitive part/ full-time employment is relatively poor.…”
mentioning
confidence: 99%